Travel Inscription of Bosnia and Bosnian in the 19th Century - Hadžiefendić-Parić, Remzija; Samajić, Ramiza (Poznańskie Studia Slawistyczne, 2023)
The topic is romantic travelogues with the subject of Bosnia: descriptions and insights into the perceived “reality” of the Bosnian area and people of the19th century presented through linguistic and stylistic means and on examples of selected travelogues from that period. New historical experiences of the writer opened the way for the emotional reception of collective practices of people, and this often leads to ahistorical conceptualization and long-lasting stereotypes. Considering that both linguistic activity and historical memory are mutual psychological processes, the diverse strategic character of the travel discourse through research shows that known cultural patterns can often deceive with their simplified form.